High‐Intensity Statin Therapy Is Associated With Improved Survival in Patients With Peripheral Artery Disease. Issue 7 (15th July 2017) - Raymond Foley, T.; Singh, Gagan D.; Kokkinidis, Damianos G.; Choy, Ho‐Hin K.; Pham, Thai; Amsterdam, Ezra A.; Rutledge, John C.; Waldo, Stephen W.; Armstrong, Ehrin J.; Laird, John R.
Abstract : Background: The relative benefit of higher statin dosing in patients with peripheral artery disease has not been reported previously. We compared the effectiveness of low‐ or moderate‐intensity (LMI) versus high‐intensity (HI) statin dose on clinical outcomes in patients with peripheral artery disease. Methods and Results: We reviewed patients with symptomatic peripheral artery disease who underwent peripheral angiography and/or endovascular intervention from 2006 to 2013 who were not taking other lipid‐lowering medications. HI statin use was defined as atorvastatin 40–80 mg or rosuvastatin 20–40 mg. Baseline demographics, procedural data, and outcomes were retrospectively analyzed. Among 909 patients, 629 (69%) were prescribed statins, and 124 (13.6%) were treated with HI statin therapy. Mean low‐density lipoprotein level was similar in patients on LMI versus HI (80±30 versus 87±44 mg/dL, P =0.14). Demographics including age (68±12 versus 67±10 years, P =0.25), smoking history (76% versus 80%, P =0.42), diabetes mellitus (54% versus 48%, P =0.17), and hypertension (88% versus 89%, P =0.78) were similar between groups (LMI versus HI). There was a higher prevalence of coronary artery disease (56% versus 75%, P =0.0001) among patients on HI statin (versus LMI). After propensity weighting, HI statin therapy was associated with improved survival (hazard ratio for mortality: 0.52; 95% confidence interval, 0.33–0.81; P =0.004) and decreased major adverse cardiovascular events (hazard ratio: 0.58; 95% confidence interval 0.37–0.92, P =0.02). Conclusions: In patients with peripheral artery disease who were referred for peripheral angiography or endovascular intervention, HI statin therapy was associated with improved survival and fewer major adverse cardiovascular events compared with LMI statin therapy.